2003
DOI: 10.1034/j.1600-0897.2003.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Cytokine Concentration in Follicular Fluid of Poor and High Responder Patients and their Influence of ICSI‐outcome

Abstract: There was no significant difference between IGF-I, IL-6, IL-8, EGF and GM-CSF concentrations of low and high responder patients. Besides, PDGF was significantly (P = 0.007) higher in high responder compared with low responder patients. Moreover, in poor responder patients, a negative correlation was found between PDGF and fertilization rate. However, the cytokine levels in FF of the patients undergoing controlled ovarian hyperstimulation for ICSI could not be used as a marker of oocyte fertilization and implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
1
14
1
1
Order By: Relevance
“…No correlation was found by previous investigators (13)(14)(15) between IL-8 concentration and fertilization rates, PRs, or IVF/ICSI outcome. Our results concur with these studies.…”
Section: Figurecontrasting
confidence: 55%
See 2 more Smart Citations
“…No correlation was found by previous investigators (13)(14)(15) between IL-8 concentration and fertilization rates, PRs, or IVF/ICSI outcome. Our results concur with these studies.…”
Section: Figurecontrasting
confidence: 55%
“…Previous studies have demonstrated the presence of IL-8 within human ovarian follicular fluid (FF) of both IVF patients (6,(11)(12)(13)(14)(15) and normally cycling patients (8,12). Most of these previous studies have measured cytokine levels in pooled FF samples without taking into account that the levels detected may vary based on the size of the follicle.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Conversely, in another study, serum IL-6 levels were found to be correlated negatively with E2 levels (17). FF IL-6 concentrations were also compared between low and high responder patients undergoing ART, and no difference was found (20). In our study, the peak serum E2 levels were similar between the two groups and we did not include the PCOS cases in the study.…”
Section: Student's T-testmentioning
confidence: 54%
“…The extent to which the follicular microenvironment affects oocyte competence and as 27,28 . Biochemical analysis of human follicular fluid obtained in stimulated cycles has demonstrated significant differences in concentrations of steroids, growth factors, enzymes and cytokines among follicles at oocyte recovery time 29,30 . This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%